Research on Path Planning of Unmanned Mine Truck in Open-pit Mine Based on Vehicle-road Coordination - Zhang, Lincong; Chen, Tingjin (2024 2nd International Conference on Signal Processing and Intelligent Computing (SPIC), 2024)
To facilitate the implementation of unmanned trucks in open-pit mines, this paper explores the essential technologies for path planning for unmanned truck. It proposes a novel research approach, advocating for the organic integration of vehicle-road cooperation and path planning for unmanned truck. And this paper proposes a R-PSO algorithm based on return value for the sudden accident in the open-pit mine area. The simulation results show that the algorithm has better optimization ability, faster convergence speed and shorter time consumption than the traditional algorithm.